2013
DOI: 10.1136/jmedgenet-2013-101695
|View full text |Cite
|
Sign up to set email alerts
|

An overview on molecular biology of KIT/PDGFRA wild type (WT) gastrointestinal stromal tumours (GIST)

Abstract: Large series of patients are required for defining the biological fingerprint of each subtype and integrating it with clinical data. This will allow the transfer of biological information to clinical practice and its use as an additional tool for diagnosis, prognosis and selection of medical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 81 publications
1
69
2
5
Order By: Relevance
“…Despite the fact that this latter tumor type has never been associated with SDH deficiency, we showed loss of SDHB expression in one of the aforementioned ACCs, but without any germline SDH-x pathogenic mutations or gross deletions detected. This finding further extends the spectrum of tumors displaying loss of SDHB and/or SDHA expression in the absence of causative SDH-x mutations, including a clinicopathologically and biologically distinctive subset of KIT/PDGFRA WT GISTs (Barletta & Hornick 2012, Nannini et al 2013, poorly and/or un-differentiated NBLs (Feichtinger et al 2010), and a clear cell RCC with sarcomatous dedifferentiation (Papathomas et al 2013).…”
Section: Discussionmentioning
confidence: 95%
“…Despite the fact that this latter tumor type has never been associated with SDH deficiency, we showed loss of SDHB expression in one of the aforementioned ACCs, but without any germline SDH-x pathogenic mutations or gross deletions detected. This finding further extends the spectrum of tumors displaying loss of SDHB and/or SDHA expression in the absence of causative SDH-x mutations, including a clinicopathologically and biologically distinctive subset of KIT/PDGFRA WT GISTs (Barletta & Hornick 2012, Nannini et al 2013, poorly and/or un-differentiated NBLs (Feichtinger et al 2010), and a clear cell RCC with sarcomatous dedifferentiation (Papathomas et al 2013).…”
Section: Discussionmentioning
confidence: 95%
“…In particular, it has been shown that deletions of KIT exon 11, especially those involving codon 557 and/or codon 558 (designated as KITdel-inc557/558), are associated with malignant behavior (11)(12)(13)(14). Conversely, KIT/PDGFRA WT GIST and most PDGFRA-mutated GIST generally have a lower potential for malignancy (2,15). However, the available data are still insufficient to be incorporated into routine clinical risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10% to 15% of adult GIST and 85% of pediatric GIST, defined as KIT/PDGFRA "wild type" (WT), lack KIT or PDGFRA mutations. These tumors are highly heterogeneous and profoundly different from KIT/PDGFRA-mutated GIST in terms of clinical behavior and molecular profiles, and they are now considered as separate pathologic entities (2).…”
Section: Introductionmentioning
confidence: 99%
“…[68][69][70] The extent of surgery should be determined on a case-by-case basis, taking into account the risk of recurrence, the lack of benefit from available tyrosine kinase inhibitors, and the actual behavior of the underlying disease.…”
Section: Gastrointestinal Stromal Tumorsmentioning
confidence: 99%